2000
DOI: 10.1111/j.1471-0528.2000.tb13242.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperechogenic fetal bowel: a prospective analysis of sixty consecutive cases

Abstract: A two year prospective analysis of all second trimester fetuses (16-22 weeks of gestation) with hyperechogenic bowel was undertaken. Hyperechogenic fetal bowel (sonographic echogenicity similar to or greater than that of surrounding fetal bone) was diagnosed using strict criteria. Outcome of affected fetuses was ascertained from hospital records, health care workers and autopsy reports, up to six months of age. Sixty consecutive fetuses were identified, of which 48 (80%) were liveborn. Six pregnancies were ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 11 publications
(29 reference statements)
3
24
0
2
Order By: Relevance
“…These findings are similar to the results of the current study with respect to the rate of prenatal demise and the high incidence of normal birth in children with HB. Another study by Ghose, et al reported similar results with 82% of the fetuses with isolated HB in their study having normal outcome (7). …”
Section: Discussionsupporting
confidence: 64%
“…These findings are similar to the results of the current study with respect to the rate of prenatal demise and the high incidence of normal birth in children with HB. Another study by Ghose, et al reported similar results with 82% of the fetuses with isolated HB in their study having normal outcome (7). …”
Section: Discussionsupporting
confidence: 64%
“…CF has been reported in 2.5-9.9% of cases of hyperchogenic bowel (Corteville et al 1996;Ghose et al 2000;Muller et al 1998Muller et al , 2002Scotet et al 2002;Slotnick and Abuhamad 1996). In a large series of 641 pregnancies reported by Muller et al, CF accounted for 3.1% of fetal bowel anomalies and 20/21 cases with two CFTR mutations had ''severe'' genotypes associated with classical CF (Muller et al 2002).…”
Section: Introductionmentioning
confidence: 93%
“…(27) Previous reports have also suggested an increased incidence of intrauterine growth restriction (IUGR) and intrauterine fetal demise (IUFD) in fetuses with echogenic bowel, with reported incidences ranging from 14.0–23.3% for IUGR and from 3.8–8.0% for IUFD. (711) Fetal redistribution of blood flow to vital organs with resultant bowel hypoperfusion and ischemia is the proposed explanation for the hyperechoic appearance of the fetal bowel in these situations. (8,10,12)…”
Section: Introductionmentioning
confidence: 99%